Acquired FXIII Deficiency is Associated with High Morbidity - Duque, Patricia; Chasco-Ganuza, Maite; Ortuzar, Ariana; Almaraz, Carolina; Terradillos, Estrella; Perez-Rus, Gloria; Pascual, Cristina (Thrombosis and Haemostasis, 2021)
Background A factor XIII (FXIII) level >30% is considered necessary to prevent spontaneous bleeding. Bleeding is also a risk in patients with acquired FXIII deficiency, but the hemostatic level of FXIII in this context remains to be determined.Methods We retrospectively analyzed all patients diagnosed with acquired FXIII deficiency at a large hospital over 3 years (study ID NCT04416594, http://www.clinicaltrials.gov) and assessed clinical data to identify the best cut-off point for FXIII activity to distinguish between low and high risk of major bleeding in a mixed medical and surgical population.Results Of the 97 patients who experienced bleeding despite a normal coagulation test, 43.2% had FXIII activity <70%. FXIII activity was significantly lower in surgical patients and patients admitted to the intensive care unit (ICU). Low FXIII activity was significantly associated with long ICU stays and a high incidence of major bleeding.Conclusion Acquired FXIII deficiency is associated with high morbidity. The hemostatic level of FXIII in the setting of acquired FXIII deficiency might be above 30%.
Keywords: FXIII deficiency; hemorrhage; morbidity; blood transfusion; postoperative